The development of pre-service biology teachers' intention to use digital incremental scaffolds: insights from guided online training - Offermann, Margit; Karbstein, Rebekka; Lohrsträter, Ricarda; Großmann, Nadine; Großschedl, Jörg; Gussen, Lea; Kleinert, Svea Isabel; Schaal, Steffen; Schaldach, Pascal; Wilde, Matthias (Frontiers in Psychology, 2025)
IntroductionIn an increasingly digital educational landscape, it is essential that teachers not only possess subject-specific knowledge but are also able to integrate digital tools in their teaching. This study investigates the impact of an asynchronous digital teacher training course on pre-service biology teachers' behavioral intentions regarding the implementation of digital incremental scaffolds. Based on the Theory of Planned Behavior (TPB) and the Technological Pedagogical and Content Knowledge (TPACK) framework, this study explores psychological and pedagogical factors that predict such behavioral changes.MethodsAs an intervention, an iMooX-hosted training comprised eight modules, divided into an introductory unit, a basic module and three advanced modules to support the development and implementation of digital incremental scaffolds in biology lessons. A total of 100 German pre-service biology teachers (M = 23.4 years, SD = 3.5, 86% female) participated in this quasi-experimental pre-post intervention study as part of their university curriculum. They completed standardized self-reporting questionnaires before and after engaging in the 3-h asynchronous digital teacher training course. The test instruments assessed constructs from the TPB and TPACK frameworks. Paired t-tests and structural equation modeling were used for data analysis.ResultsThere were significant increases across all sub-dimensions of the TPB, with the highest effective sizes in attitude (d = 0.86) and self-efficacy (d = 1.33); as well as behavioral intention itself (d = 0.80) and TPACK (d = 0.70). A regression analysis showed that attitude (β = 0.66, p < 0.001) and subjective norm (β = 0.18, p < 0.01) significantly predicted behavioral intention, while TPACK (β = 0.35, p < 0.001) and attitude (β = 0.57, p < 0.001) significantly predicted self-efficacy.DiscussionThese findings support the relevance of internal beliefs and social expectations in driving pre-service teachers' intention to integrate digital tools. The results also emphasize the importance of pedagogical-technological knowledge in shaping teachers' confidence in implementing such digital tools. The study's implications for designing practical informed digital training formats in teacher education are discussed.